Systematic review and meta-analysis of studies in which burrowing behaviour was assessed in rodent models of disease-associated persistent pain: systematic review and meta-analysis - Zhang, Xue Ying; Barakat, Ahmed; Diaz-delCastillo, Marta; Vollert, Jan; Sena, Emily S.; Heegaard, Anne-Marie; Rice, Andrew S. C.; Soliman, Nadia (Pain, 2022)
Burrowing behaviour is used to assess pain-associated behaviour in laboratory rodents. To gain insight into how models of disease-associated persistent pain and analgesics affect burrowing behaviour, we performed a systematic review and meta-analysis of studies that assessed burrowing behaviour. A systematic search in March 2020 and update in September 2020 was conducted in 4 databases. Study design characteristics and experimental data were extracted, followed by a random-effects meta-analysis. We explored the association between burrowing and monofilament-induced limb withdrawal. Dose response relationship was investigated for some analgesics. Forty-five studies were included in the meta-analysis, in which 16 model types and 14 drug classes were used. Most experiments used rat (79%) and male (72%) animals. Somatic inflammation and trauma-induced neuropathy models were associated with reduced burrowing behaviour. Analgesics (nonsteroidal anti-inflammatory drug and gabapentinoids) attenuated burrowing deficits in these models. Reporting of measures to reduce risk of bias was unclear except for randomisation which was high. There was not a correlation (R2 = 0.1421) between burrowing and monofilament-induced limb withdrawal. Opioids, gabapentin, and naproxen showed reduced burrowing behaviour at high doses, whereas ibuprofen and celecoxib showed opposite trend. The findings indicate that burrowing could be used to assess pain-associated behaviour. We support the use of a portfolio of composite measures including spontaneous and stimulus-evoked tests. The information collected here could help in designing experiments involving burrowing assessment in models of disease-associated pain.
Online verfügbar: 29 March 202
Gesehen am 31.07.2023